Srs2 mediates PCNA-SUMO-dependent inhibition of DNA repair synthesis - Burkovics, Peter; Sebesta, Marek; Sisakova, Alexandra; Plault, Nicolas; Szukacsov, Valeria; Robert, Thomas; Pinter, Lajos; Marini, Victoria; Kolesar, Peter; Haracska, Lajos; Gangloff, Serge; Krejci, Lumir (EMBO journal, 2013)
Completion of DNA replication needs to be ensured even when challenged with fork progression problems or DNA damage. PCNA and its modifications constitute a molecular switch to control distinct repair pathways. In yeast, SUMOylated PCNA (S-PCNA) recruits Srs2 to sites of replication where Srs2 can disrupt Rad51 filaments and prevent homologous recombination (HR). We report here an unexpected additional mechanism by which S-PCNA and Srs2 block the synthesis-dependent extension of a recombination intermediate, thus limiting its potentially hazardous resolution in association with a cross-over. This new Srs2 activity requires the SUMO interaction motif at its C-terminus, but neither its translocase activity nor its interaction with Rad51. Srs2 binding to S-PCNA dissociates Polδ and Polη from the repair synthesis machinery, thus revealing a novel regulatory mechanism controlling spontaneous genome rearrangements. Our results suggest that cycling cells use the Siz1-dependent SUMOylation of PCNA to limit the extension of repair synthesis during template switch or HR and attenuate reciprocal DNA strand exchanges to maintain genome stability.
Keywords: DNA Polymerase III; SUMO-1 Protein; DNA Polymerase II; sumoylace; Mutation; protein SUMO-1; homologní rekombinace; Sumoylation; replikace DNA; nestabilita genomu; ultrafialové záření; Homologous Recombination; Proliferating Cell Nuclear Antigen; Saccharomyces cerevisiae; poškození DNA; DNA Helicases; proliferační antigen buněčného jádra; DNA Damage; rekombinasa Rad51; DNA Replication; Rad51 Recombinase; Ultraviolet Rays; Saccharomyces cerevisiae - proteiny; DNA-polymerasa III; DNA-polymerasa II; DNA Repair; oprava DNA; DNA-helikasy; mutace; Genomic Instability; Saccharomyces cerevisiae Proteins